Application of imidacloprid controlled-release granules to enhance the utilization rate and control wheat aphid on winter wheat - Wan-ling YUAN; Bo XU; Gang-chao RAN; Hui-ping CHEN; Peng-yue ZHAO; Qi-liang HUANG (Journal of Integrative Agriculture, 2020)
During winter wheat production, aphids need to be controlled with pesticides for the entire growth period. Controlled-release technology has been regarded as an alternative method for the improvement of pesticide efficiency. This study investigated two types of imidacloprid controlled-release granule (CR-GR): 2% imidacloprid CR-GR and 0.2% imidacloprid pesticide-fertilizer controlled-release granule (PF-CR-GR) when wheat was sown in winter. The release performance, utilization rate, terminal residues in edible parts, control effect on aphids, and achieved winter wheat yield were evaluated for both laboratory experiments and field application. Imidacloprid PF-CR-GR released more quickly in aqueous medium than CR-GR because of its good water solubility. After CR-GR treatments, the concentrations in wheat roots and soil were similar throughout the entire sampling period, and the concentrations in shoots were about 10–20% of those in roots. Imidacloprid was better absorbed when CR-GR was used as root treatment, compared with foliar treatment. Field application showed that imidacloprid CR-GR and PF-CR-GR controlled aphids throughout the entire growth period of winter wheat and improved the wheat yield. These findings identified application of imidacloprid CR-GR and PF-CR-GR on winter wheat as an effective way to enhance the pesticide utilization rate and ensure adequate yield. This paper provides a theoretical basis for the scientific use of pesticides and guides scientific pesticide application.